Social Stimulus Causes Aberrant Activation of the Medial Prefrontal Cortex in a Mouse Model With Autism-Like Behaviors - Pirone, Antonella; Alexander, Jonathan M.; Koenig, Jenny B.; Cook-Snyder, Denise R.; Palnati, Medha; Wickham, Robert J.; Eden, Lillian; Shrestha, Neha; Reijmers, Leon; Biederer, Thomas; Miczek, Klaus A.; Dulla, Chris G.; et al. (Frontiers in Synaptic Neuroscience, 2018)
Autism spectrum disorder (ASD) is a highly prevalent and genetically heterogeneous brain disorder. Developing effective therapeutic interventions requires knowledge of the brain regions that malfunction and how they malfunction during ASD-relevant behaviors. Our study provides insights into brain regions activated by a novel social stimulus and how the activation pattern differs between mice that display autism-like disabilities and control littermates. Adenomatous polyposis coli (APC) conditional knockout (cKO) mice display reduced social interest, increased repetitive behaviors and dysfunction of the β-catenin pathway, a convergent target of numerous ASD-linked human genes. Here, we exposed the mice to a novel social versus non-social stimulus and measured neuronal activation by immunostaining for the protein c-Fos. We analyzed three brain regions known to play a role in social behavior. Compared with control littermates, APC cKOs display excessive activation, as evidenced by an increased number of excitatory pyramidal neurons stained for c-Fos in the medial prefrontal cortex (mPFC), selectively in the infralimbic sub-region. In contrast, two other social brain regions, the amygdala and piriform cortex show normal levels of neuron activation. Additionally, APC cKOs exhibit increased frequency of miniature excitatory postsynaptic currents (mEPSCs) in layer 5 pyramidal neurons of the infralimbic sub-region. Further, immunostaining is reduced for the inhibitory interneuron markers parvalbumin and somatostatin in the APC cKO mPFC. Our findings suggest aberrant excitatory-inhibitory balance and activation patterns. As β-catenin is a core pathway in ASD, we identify the infralimbic sub-region of the mPFC as a critical brain region for autism-relevant social behavior.